Moral panics and violent street crime 1750-2000: A comparative perspective - King, Pete (2003)
About the book: This book aims to both reflect and take forward current thinking on comparative and cross-national and cross-cultural aspects of the history of crime. Its content is wide-ranging: some chapters discuss the value of comparative approaches in aiding understanding of comparative history, and providing research directions for the future; others address substantive issues and topics that will be of interest to those with interests in both history and criminology. Overall the book aims to broaden the focus of the historical context of crime and policing to take fuller account of cross-national and cross-cultural factors